Peritoneal Dialysis Access: Open versus Laparoscopic Surgical Techniques. Issue 4 (October 2013) - Hwang, Christine; Davidson, Ingemar; Santarelli, Stefano; Zeiler, Matthias; Ceraudo, Emilio; Pedone, Meri; Saxena, Ramesh; Slakey, Douglas; Wade, Melissa; Gallieni, Maurizio
Aim: To outline pros and cons with the open and laparoscopic techniques when placing peritoneal dialysis (PD) catheters. Background: Controversy exists regarding which technique, the open and laparoscopic, if any, is superior to the other. In addition, there is the question of which approach is best in rescuing malfunctioning PD catheters. Results: Rather than promoting one doctrine fits all, philosophically, doing the right thing for the patient by specific criteria is ethically the better model. These specific selection criteria include patient characteristics, the team's skills and knowledge and institutional resources and commitment. Also, the sophistication of a PD unit for training and monitoring of patients is crucial for successful outcomes. Open paramedian and two laparoscopic approaches are described in detail, outlining advantages and disadvantages of each, with suggestions when one method is preferred. Conclusions: In general, the laparoscopic technique is associated with longer operative times, higher costs and the need to utilize general anesthesia. It is, however, the preferred method when rescuing malfunctioning catheters and may increase the PD patient population in patients with previous abdominal surgeries. The dialysis access surgeon should be familiar with both open and laparoscopic techniques and appropriately choose the ideal method based upon the individual patient and institutional resources.